Landscape design education: challenges and proposals. - Freire, Maria da Conceição (2014)
Landscape design is central in landscape architectural education. Teaching landscape design can’t be just an execution of various landscape projects, where the teacher's role is more a practitioner and less an educator. We have to bring together, with the technical and disciplinary components, the pedagogic, methodological and psychological ones. Those conditions determine to deal with different domains, teaching strategies and opportunities. My doctoral research in teaching landscape design, called attention for the importance to think about current practices and to create creative and sensible ways to improve it, trying to work against the prevailing conservative attitudes and routines. I reproduce here some proposals, related with pedagogical and methodological issues.